2018
DOI: 10.1016/j.neuropharm.2017.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry & the psychedelic drugs. Past, present & future

Abstract: a b s t r a c tThe classical psychedelic drugs, including psilocybin, lysergic acid diethylamide and mescaline, were used extensively in psychiatry before they were placed in Schedule I of the UN Convention on Drugs in 1967. Experimentation and clinical trials undertaken prior to legal sanction suggest that they are not helpful for those with established psychotic disorders and should be avoided in those liable to develop them. However, those with so-called 'psychoneurotic' disorders sometimes benefited consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
222
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(244 citation statements)
references
References 118 publications
4
222
0
18
Order By: Relevance
“…Especially in the latter patient group, this may shift the risk-benefit ratio against psychedelic interventions. In line with this, pre-prohibition clinical studies, which tested psychedelics for mental disorders across the board, found positive results mostly in (then so-called) "psychoneurotic" disorders (105).…”
Section: Clinical Targetsmentioning
confidence: 67%
“…Especially in the latter patient group, this may shift the risk-benefit ratio against psychedelic interventions. In line with this, pre-prohibition clinical studies, which tested psychedelics for mental disorders across the board, found positive results mostly in (then so-called) "psychoneurotic" disorders (105).…”
Section: Clinical Targetsmentioning
confidence: 67%
“…For example, high doses of Selective Serotonin Reuptake Inhibitors (SSRIs), exposure, and response treatment are effective for people in the later stages of OCD [132], which has also been recently conceptualized within a staging framework [133]. In addition, there is interest in pharmacological approaches that are being used for treatment-resistant depression, such as ketamine and psilocybin [134]. Interestingly, ketamine showed some promise in a small series of studies in the 1990s [135].…”
Section: Treatment-resistant Depression and Other Co-morbidities As Mmentioning
confidence: 99%
“…In the long‐term, in order for psilocybin treatment to become established practice, rescheduling from Schedule I needs to be achieved and specific training for psychedelic therapy must be developed, standardised and licensed to maintain patient safety and efficacy of treatment (Carhart‐Harris et al, 2018b; Rucker, Iliff, & Nutt, 2018). Despite the growing awareness of their potential therapeutic capabilities many regulatory authorities continue to consider these compounds to be controversial (Nutt, 2014).…”
Section: Concluding Commentsmentioning
confidence: 99%